African Universities and Industry Partnership for Quality Higher Education: Global Framework for Graduate Attributes - Francis Ennin; Karanam Pushpanadham (International Journal of Scientific Research and Innovative Studies, 2024)
Education, in general, and higher education specifically, should aim to empower learners to better themselves personally and make society a better place for its inhabitants through research and societal impact. Achieving such a feat entails equipping graduates with the right attitudes for proper professional development to impact society. Educational institutions partnering with industries is a sure way to achieve what education intends. Industries are significant stakeholders of the labour market and, as such, can go a long way to help educational institutions develop the right skills needed for job placement and entrepreneurship. This study explores the partnership between Higher Education Institutions (HEIs) and industry, the required steps, and global issues impacting graduate attitudes. The study outlines the need to implement a need-based curriculum, involve good graduate attitudes in academic planning through value-added courses, lifelong learning, involvement of digital resources and the creation of international networks among universities. Keywords: University and Industry Partnership, Graduate Attitudes, Policy Framework, Quality High Education